2007
DOI: 10.1007/s12116-007-9002-8
|View full text |Cite
|
Sign up to set email alerts
|

Social Capability, History and the Economies of Communist and Postcommunist States

Abstract: Studies show that in non-Communist developed and developing countries earlier development of agriculture, a dense population, and a state-level polity is associated with a higher income and more rapid economic growth in the late twentieth century. We investigate whether this was also the case for countries under communism and for the same countries in transition to a market economy. Our findings are generally affirmative, with an interesting pattern for the Eurasian socialist core countries involving higher gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Bockstette et al's data were subsequently expanded to include more ex-Communist countries (Iliev and Putterman 2007), more African countries (Cinyabuguma and Putterman 2011), and a few other countries for which complementary income or other required data had initially been viewed as unreliable. Based on this extended dataset, Putterman and Weil (2010) demonstrated that the ability of state history to predict current levels of development is greatly strengthened by replacing the state history that transpired on a given country's territory by the weighted average state history of the places in which current residents' ancestors lived in the past.…”
Section: State History and Economic Developmentmentioning
confidence: 99%
“…Bockstette et al's data were subsequently expanded to include more ex-Communist countries (Iliev and Putterman 2007), more African countries (Cinyabuguma and Putterman 2011), and a few other countries for which complementary income or other required data had initially been viewed as unreliable. Based on this extended dataset, Putterman and Weil (2010) demonstrated that the ability of state history to predict current levels of development is greatly strengthened by replacing the state history that transpired on a given country's territory by the weighted average state history of the places in which current residents' ancestors lived in the past.…”
Section: State History and Economic Developmentmentioning
confidence: 99%
“…Roughly the same data set was also used by Chanda and Putterman (2005), and Chanda and Putterman (2007). Bockstette et al's data were subsequently expanded to include more ex-Communist countries (Iliev and Putterman 2007), more African countries (Cinyabuguma and Putterman 2011), and a few other countries for which complementary income or other required data had initially been viewed as unreliable. Based on this extended dataset, Putterman and Weil (2010) demonstrated that the ability of state history to predict current levels of development is greatly strengthened by replacing the state history that transpired on a given country's territory by the weighted average state history of the places in which current residents' ancestors lived in the past.…”
Section: Literature Review 21 State History and Economic Developmentmentioning
confidence: 99%
“…Technologies are usually developed according to the requirements of the country in which such technologies have first evolved. However, the formation of the appropriate human capital can, to some extent, overcome such gaps of technological incongruence and hence enhances the social capability of the recipient country (Dahlman and Perkins, 1995;Koo and Perkins, 1995;OECD, 2001;Iliev and Putterman, 2007). The greater the absorptive capacity, the greater the effectiveness of FDI and incoming spillovers will be on productivity.…”
Section: Human Capital Randd and Technology Transfermentioning
confidence: 99%